2014
DOI: 10.1038/ki.2014.96
|View full text |Cite
|
Sign up to set email alerts
|

Cannulation technique influences arteriovenous fistula and graft survival

Abstract: Hemodialysis patient survival is dependent on the availability of a reliable vascular access. In clinical practice, procedures for vascular access cannulation vary from clinic to clinic. We investigated the impact of cannulation technique on arteriovenous fistula and graft survival. Based on an April 2009 cross-sectional survey of vascular access cannulation practices in 171 dialysis units, a cohort of patients with corresponding vascular access survival information was selected for follow-up ending March 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
124
2
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(149 citation statements)
references
References 22 publications
(27 reference statements)
8
124
2
15
Order By: Relevance
“…This opinion is in agreement with Parisotto et al. , who believe that needle rotation is unnecessary, and the technique may cause additional trauma to the blood vessel. It was also shown that a rotated needle draws 42% of the core flow through the back eye, whereas the inserted position draws 36%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This opinion is in agreement with Parisotto et al. , who believe that needle rotation is unnecessary, and the technique may cause additional trauma to the blood vessel. It was also shown that a rotated needle draws 42% of the core flow through the back eye, whereas the inserted position draws 36%.…”
Section: Discussionsupporting
confidence: 91%
“…Focus has been directed at maintaining the patency of the vascular access . Cannulation technique has a large influence on some of the factors that affect patency but has received little attention.…”
mentioning
confidence: 99%
“…The recirculation values available for this study were all measured with the thermal dilution method, which measures the sum of cardiopulmonary recirculation and access recirculation, and so tend to be higher than pure VA flow measurements. On the other hand, recirculation values were measured, according to protocol, at Qb = 300 mL/min, and higher recirculation is probable at higher flows and depending on the cannulation technique exercised . Other possible explanations for why Qb >390 mL/min is associated with higher risk of AVF failure are related to needle size.…”
Section: Discussionmentioning
confidence: 99%
“…In hemodialysis patients with an arteriovenous fistula, prolonged bleeding usually ceases under extended pressure after 20–30 minutes. Therefore, a puncture‐technique changing the holes and inserting the needle with bevel‐up should be preferred . It is not known how many venous punctures will cause scars in plasma donors, but it would be an interesting question for further research in plasma donations, which may be limited because of obliterated veins by scarring (Figure ).…”
Section: Bleedingmentioning
confidence: 99%